Rare : portraits of America's endangered species - Sartore, Joel. (Washington, D.C. : National Geographic, 2010)
Sartore and National Geographic present 80 iconic images, representing a lifelong commitment to the natural world and a three-year investigation into the Endangered Species Act along with the creatures it exists to protect.
Foreword / by Joel Sartore -- Last one / by Verlyn Klinkenborg -- [more than] 10,000 : living population more than 10,000 individuals -- 10,000 - 1,000 : living population between 10,000 and 1,000 individuals -- [less than] 1,000 : living population fewer than 1,000 individuals -- ? : living population numbers unknown -- On the rise : living population numbers increasing -- Taking action -- List of species -- Taking the photos -- About the authors.
Includes bibliographical references and index.
Keywords: Endangered species -- United States; Endangered species -- United States -- Pictorial works